Water permeability of cracked strain-hardening cement-based composites. (September 2017) - Wagner, Christian; Villmann, Beate; Slowik, Volker; Mechtcherine, Viktor
Abstract: Strain-hardening cement-based composites (SHCC) are characterized by the formation of numerous fine cracks under tensile loading. The water permeability of the cracked material and, consequently, the durability of respective structural members will strongly depend on these cracks. Experimental investigations into the water permeability of both SHCC specimens pre-cracked under uniaxial tension and SHCC overlays on cracked concrete substrate were performed. It is proposed to determine certain crack pattern parameters which may be linked to the theoretical water permeability of the cracked material. For this linking, a weighting function for the observed crack widths has been derived on the basis of the Hagen-Poiseuille equation.